Upper Quarter Y Balance Test: reliability and performance comparison between genders in active adults - Gorman, Paul P; Butler, Robert J; Plisky, Phillip J; Kiesel, Kyle B (Journal of strength and conditioning research, 2012)
The inclusion of movement tests before performance training and sport participation is gaining popularity as part of musculoskeletal screening for injury. The identification of an athlete's asymmetries and poor performance in the preseason allows coaches and sports medicine clinicians the opportunity to proactively address these deficits to reduce the potential for injury. Currently, there are no tests reported in the literature that simultaneously require shoulder and core stability while taking the subjects through a large range of motion at the end range of their stability. Thus, the purpose of this article was to describe the Upper Quarter Y Balance Test and report the gender differences in the performance of the test. Upper extremity reach distances were measured in 95 active adults using a standardized upper extremity balance-and-reach protocol. Intraclass correlation coefficients were used to assess reliability, and gender differences were analyzed using an independent samples t-test, whereas bilateral differences were analyzed using a dependent samples t-test for the normalized composite reach scores. Intraclass correlation coefficient (3.1) for test-retest reliability ranged from 0.80 to 0.99. Intraclass correlation coefficient (3.1) for interrater reliability was 1.00. Average composite scores (right/left) reported as a percentage of limb length were 81.7/82.3% for men and 80.7/80.7% for women. The results of the study suggest that the Upper Quarter Y Balance Test is a reliable test for measuring upper extremity reach distance while in a closed-chain position. It was further determined that there was no significant difference in performance between genders or between sides on the test when normalized to limb length. Coaches and sports medicine professionals may consider incorporating the Upper Quarter Y Balance Test as part of their preprogram testing to identify movement limitations and asymmetries in athletes and thereby may reduce injury.